SCHIZOPHRENIA AS AN AESTHETIC DEVICE OF A LITERARY WORK - Nur Hasanah (Jurusan Sastra Indonesia, 2019)
This study aims to reveal the aesthetic language of schizophrenia that contains in the literary work. The problem discussed is how the emergence of schizophrenia as a new phenomenon in a literary aesthetic is and the application of schizophrenia in literary works. The theory used is the theory of postmodernism. Based on the results obtained, schizophrenia, which firstly is a psychoanalysis term to refer to a disease characterized by the splitting of personality identity in the human mentality, was apparently used in the language of a literary aesthetic. The term is then used as a language aesthetic tool in literary works. Literary works containing schizophrenia are seen in poetry and prose.